The Effect of Organic Waste Combination in Feed Medium on the Growth and Development of Hermetia illucens Larvae - Corani, Bernadetha Chanelia Dwi; Suhandoyo (Jurnal Sains Dasar, 2025)
This study aims to determine the effect of a combination of fermented tofu pulp, coconut pulp, rice bran, and cabbage waste on: 1) the growth and; 2) development of BSF larvae. The study was conducted using a completely randomized design (CRD) at the Biology Garden of the Faculty of Mathematics and Natural Sciences, Yogyakarta State University. The independent variables used were combinations of feed media with fermented tofu pulp, cabbage waste, coconut pulp, and rice bran in 3 treatments. The dependent variables observed were growth, including biomass increase and individual larval growth, as well as BSF larval development. The control variables of the study were container size, initial BSF larva biomass, and BSF larva age, which was 10 days after hatching. Observations of individual growth and BSF larva development were conducted once a week. BSF larva biomass measurements were conducted every 2 weeks using the gravimetric method. Data analysis for this study used ANOVA and Duncan's Multiple Range Test (DMRT). The combination of fermented tofu pulp, coconut pulp, rice bran, and cabbage waste had a significant effect (P<0.05) on the increase in biomass and individual growth of BSF larvae, as well as on the speed of BSF larvae development into pupae.